2013
DOI: 10.1111/pme.12135
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pain Control Challenges with Buprenorphine/Naloxone Therapy in a Patient with Compartment Syndrome Secondary to McArdle's Disease: A Case Report and Review

Abstract: Buprenorphine/naloxone is being prescribed off-label with increasing frequency for pain management in patients with or without a history of opioid abuse. Severe acute pain is more difficult to control with opioid analgesics in patients taking buprenorphine/naloxone, requiring higher than usual doses. If buprenorphine/naloxone is discontinued to better treat acute pain with other opioids, monitoring for overdose must take place for at least 72 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…High-dose hydromorphone was used successfully in several published case reports. 11 , 16 However, other authors have reported pain control ranging from poor-to-excellent with the use of hydromorphone, fentanyl, or morphine (Table 1 ). Some authors report poor pain control until discontinuation of the buprenorphine.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose hydromorphone was used successfully in several published case reports. 11 , 16 However, other authors have reported pain control ranging from poor-to-excellent with the use of hydromorphone, fentanyl, or morphine (Table 1 ). Some authors report poor pain control until discontinuation of the buprenorphine.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional teaching and most of the published literature describes a phenomenon suggesting that acute pain control is difficult for patients continued on buprenorphine therapy perioperatively or during other acute pain states. 11,[30][31][32][33] Given that buprenorphine has such high-affinity for mu-opioid receptors, traditional mu-opioid agonists (eg, morphine, fentanyl, hydromorphone, and oxycodone) are blocked from the binding necessary to facilitate adequate analgesia. The solution, in most published algorithms, has been to consider discontinuation of buprenorphine during acute pain states or before major surgery that is at least moderate in anticipated pain severity.…”
Section: Challenges Of Acute Pain Management With Buprenorphinementioning
confidence: 99%
“…Adequate pain relief was not achieved until 48 h after discontinuation of buprenorphine. 33 Another report describes a 47-yr-old woman on buprenorphine for chronic pain who underwent open window thoracoscopy for pulmonary aspergillosis. Her postoperative pain was ineffectively controlled despite high doses of intravenous hydromorphone.…”
Section: Review Of Published Reports Of Perioperative Analgesia Stratmentioning
confidence: 99%
“…35 The authors of these and other case reports suggest that buprenorphine should be discontinued at least 72 h before elective surgery and replaced with opioid agonists in the interim. 33,34,36,37 However, perioperative pain management for patients on chronic buprenorphine may be difficult regardless of whether buprenorphine is discontinued before surgery. Another report describes a 37-yr-old woman taking buprenorphine for chronic pain who underwent two separate urogynecologic procedures.…”
Section: Review Of Published Reports Of Perioperative Analgesia Stratmentioning
confidence: 99%